Diseño del cableado estructurado categoría 6 del Área Jurídica, Social y Administrativa y construcción del software del control de tráfico de internet de la UNL. - Bustillos Reyes, Hernán Alberto (2008)
his research has as main purpose to perform the design Data Network Social and Administrative Legal Department of the National University of Loja and perform software construction Access Control Internet, clearly specifying each stage, phase, norms and standards that must be met in the development of this important research project, which brings together two different procedures that are the Network Design and development of software. The research starts given the current state of the network, collecting all levels of buildings and blocks that make up the Social Area Legal and Administrative of the National University of Loja, using techniques such as interviews, surveys available, and observation, with the tabulation of this information might define requirements and features that will design the new network. Applying standards and regulations mentioned in the theoretical chapters he can establish a sober and optimal design for the Social Administrative Legal Department attached to the technological and economic reality of the period in which this research was conducted. Regarding the design of the software is necessary to establish that the application due to the requirements previously established by competent personnel. And in this research work they are clearly specified each step (analysis, design, implementation) and methodologies (ICONIX) necessary for the construction of such an important tool that aims to solve the problem of Internet access control.